Advancements in Dynamic Analysis of Reinforced Concrete Structures: A Review of Seismic and Wind Load Performance in High-Rise Buildings - Rayid Bin Abid; Preetpal Singh (Bulletin of Engineering Science, Technology and Industry, 2025)
The dynamic behavior of high-rise reinforced concrete (RC) structures under seismic and wind loads is a crucial aspect of structural engineering. This review synthesizes recent advancements in computational modeling, material assessment, and performance-based design principles. The existing research, including a case study on G+12 RC structures, highlights key parameters such as base shear, story displacement, drift ratios, and modal frequencies. While previous studies confirm the adequacy of structural designs based on national standards, a notable research gap remains in optimizing torsional effects and integrating advanced damping mechanisms. This paper critically analyzes state-of-the-art methodologies, including finite element modeling, non-destructive testing, and response spectrum analysis, to enhance structural resilience. Future prospects suggest incorporating smart materials, energy dissipation systems, and hybrid analysis techniques to further improve dynamic performance under extreme loading conditions.